THE INFLUENCE OF DOCTOR-PATIENT COMMUNICATION AND PATIENT TRUST ON INPATIENT OCCUPANCY RATE WITH WORD OF MOUTH AS AN INTERVENING VARIABLE AT X PULOMAS HOSPITAL - Valenchia Jeandry, MF. Arrozi Adhikara, Wahyuni Dian (Jurnal Cinta Nusantara, 2023)
This study aims to analyze the effect of doctor-patient communication, and patient trust in inpatient occupancy rates with word of mouth as an intervening variable at X Pulomas Hospital. The research methodology used the causality method (cause and effect relationship) and the Path Analysis method with the research design using the three box method. The sampling technique used a proportional random sampling technique for 120 respondents. The results of data processing are: doctor-patient communication has an influence on word of mouth, patient trust has an influence on word of mouth, doctor-patient communication has an influence on inpatient occupancy rates, patient trust has an influence on inpatient occupancy rates, word of mouth has an influence on the inpatient occupancy rate. Doctor-patient communication has an influence on inpatient occupancy rates with word of mouth as a mediating variable, patient trust has an influence on inpatient occupancy rates with word of mouth as a mediating variable. The findings of this study are that all variables have an influence on the inpatient occupancy rate, the variable that most influences the inpatient occupancy rate is doctor-patient communication. Word of mouth mediates the relationship between doctor-patient communication on inpatient occupancy rates and mediates the relationship between patient confidence in inpatient occupancy rates. The managerial implications of this research are approaches to DPJP and other PPA, increasing insight and knowledge, increasing collaboration between PPA, maximizing the case manager function.